ANALISIS KESALAHAN SISWA MENYELESAIKAN SOAL PEMECAHAN MASALAH POLYA - Ratu Firdausi Rahman; Iyan Rosita Dewi Nur (IKIP Siliwangi, 2021)
Students often find it difficult to work on story problems in mathematics. So that students experience many errors when answering story questions in mathematics. Analyzing students' errors according to the polya theory in completing the story is the aim of this study. Student errors contained in the polya theory, namely: understanding the problem, solving the problem, implementing the problem-solving plan and re-examining the solution obtained. The research method used is descriptive qualitative. The technique used is an interactive model data analysis from Miles & Huberman. The subjects in this study included 20 students from class VII junior high school in the neighborhood around the house. The instrument used in this research is a test in the form of problem solving and non-test with interviews. The results of the study showed that many students' mistakes were caused by a lack of understanding of the previous material so that students experienced many mistakes in planning problem solving.